Jurassic constraints on the chaotic Mars–Earth eccentricity cycle linked to the volcanically induced Jenkyns event - Yanan Fang; Paul E. Olsen; Jingeng Sha; Jessica H. Whiteside; Chengguo Guan; Masayuki Ikeda; Sha Li; Daran Zheng; Haichun Zhang; Bo Wang (Proceedings of the National Academy of Sciences, 2025)
Solar system gravitational interactions are embedded in Earth’s record of climate, providing a way to bypass the 60 Myr limit imposed by chaos. Presently with a 2.4 Myr period, the Mars–Earth beat cycle of orbital perihelion frequencies is particularly sensitive to chaotic diffusion, potentially varying by more than a million years. Early Mesozoic (252 to 145 Ma) strata provide some constraints on this cycle, with evidence of a swing through most of the solution space from 1.8 Myr at 210 Ma to 2.5 Myr at 190 Ma and back to 1.6 Myr at 180 Ma. However, only the 1.8 Myr cycle is corroborated by geochronologic data and the 1.6 Myr period is disputed. Here, we show that variations in land-plant-dominated stable carbon isotopic ratios (δ 13 C org ) from the lacustrine, paleo-high-latitude Sangonghe Formation (Junggar Basin, northwestern China), reveal at least three 1.6 Myr Mars–Earth beat cycles centered at 183 Ma, tracking atmospheric CO 2 isotopic composition in Earth’s exchangeable carbon reservoirs. Furthermore, the middle cycle includes the famous Jenkyns Event, expressed here by poleward migration of cheirolepidaceous conifers driven by CO 2 warming from the Karoo-Ferrar large igneous province (LIP). Our data do not, however, support major, LIP-triggered input of isotopically light carbon and instead support CO 2 amplification of local processes via warming and ecosystem change. Although requiring additional independent geochronological support, Sangonghe data help provide empirical constraints for filtering orbital solutions, tightening initial conditions, and testing gravitational models, as well as showing how extrinsic cyclical processes interact with a tectonic event, the Karoo-Ferrar LIP.